2019
DOI: 10.7759/cureus.4562
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Endoscopic Findings in Patients of Upper Gastrointestinal Bleeding at a Tertiary Care Hospital

Abstract: Background & aims Upper gastrointestinal bleeding (UGIB) is a common medical emergency that results in high patient morbidity and mortality. There are numerous causes of UGIB. The aim of our study was to evaluate the endoscopic findings in patients of UGIB in this part of the world. Methods This retrospective study was conducted at the Department of Gastroenterology Nishtar Medical University & Hospital Multan from June 2018 to March 2019. Record of all patients undergoing esop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 10 publications
(8 reference statements)
2
9
0
Order By: Relevance
“…Moreover, we found that UGIB was more common in male patients than females, with a male to female ratio of 1.7:1. This is the same as that of Malghani in Pakistan, and comparable to the data reported in other studies in which male patients having UGIB was greater than females, in different populations [11,13,14].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Moreover, we found that UGIB was more common in male patients than females, with a male to female ratio of 1.7:1. This is the same as that of Malghani in Pakistan, and comparable to the data reported in other studies in which male patients having UGIB was greater than females, in different populations [11,13,14].…”
Section: Discussionsupporting
confidence: 91%
“…In our study, the mean age of our patients was 48.33 years. This was slightly lower than the mean age of UGIB patients reported in other studies [9][10][11]. The majority of the patients (47%) were in the age group 41-60 years, followed by age group > 60 years (n = 212; 23%) and 26-40 years (n = 202; 22%), the least common age group was less than or equals to 25 years (n = 74; 8%).…”
Section: Discussionmentioning
confidence: 54%
“…18 The study done in Dhulikhel hospital Nepal among 90 patients of UGI bleeding, Gastric ulcer in 25.6% was the most common endoscopic finding, followed by oesophageal varices 15.6% which is similar to our study population and methods, however they have also included patient with or without previous GI bleeding. 1,9 Another study from Lahore medical college Pakistan the most common endoscopic finding was esophageal varices in 50.8% patients, followed by gastropathy in 15.6%, gastritis 9.3%, cardio-fundal varices 7.9% and duodenal ulcer 3.6% apart from our study they have analyzed every cases presenting to their hospital emergency with UGI bleeding irrespective of previous history of GI Bleeding. 9 Another study done in College of Medical science, Bharatpur showed Upper Gastrointestinal Bleeding endoscopy revealed esophageal varices 47.5%, peptic ulcer disease 33.3%, erosive mucosal disease 11.6%, Mallory Weiss tear 4.1% and malignancy 3.3%.…”
Section: Discussionmentioning
confidence: 93%
“…1 Another similar study done in Lahore Medical college Pakistan , 63.6% were male and 36.4% were female. 9 In Nepal various risk factors like smoking and alcohol consumption that are commoner in male population which might have some role in the contribution to UGI bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Dewan KR et al7 studied the clinical and endoscopic profile of acute upper gastrointestinal bleed to know the etiology, clinical presentation, severity of bleeding and outcome. 3%), erosive mucosal disease (11.6%), Mallory Weiss tear (4.1%) and malignancy (3.3%).Malghani WS et al[8] evaluated the endoscopic findings in patients of UGIB in this part of the world.They studied records of 730 (464 male and 266 females) patients undergoing EGD for UGIB. Mean age of study population was 49.38 years, similar to our study.…”
mentioning
confidence: 99%